PENDIDIKAN ISLAM DALAM PERSPEKTIF AL - QURAN SURAT AL – IMRON AYAT 138 – 139 - Arobi, Ibnul; Sa'diyah, Halimatus (LP3M UNZAH GENGGONG, 2019)
Abstract By seeing the existing reality, such as the rise of student brawl, drinking, the spread of drugs and some behaviors that deviate from religious and cultural norms, promiscuity, free sex, sexual abuse makes the role of education increasingly questionable. Education is often used as a scapegoat for failing to be said to have failed in achieving an educational objective, especially Islamic religious education which failed to print insane kamil. Ahmad D. Marimba in his book